1993
DOI: 10.1007/bf02545378
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of aromatic amino acids for antibacterial surfactants

Abstract: Five new antibacterial agents of the N‐(2‐hydroxy substituted phenoxy propyl)glycine type have been synthesized. Results of bacteriostatic tests toStaphylococcus aureus (G+) andEscherichia coli (G−) showed that ammonium cations were strongest and compounds with ap‐methylphenyl were more active than those with ao‐methylphenyl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1997
1997
1997
1997

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Combining the aromatic moiety and a-amino acid, we prepared aromatic amino acids in 1993. 4 The results of the antibacterial tests for Escherichia cola and Staphylococcus uufeus showed that the activity of these compounds in ammonium form was higher than that in carboxylic form and the compounds with prnethylphenyl group were more active than those with o-methylphenyl group. These results illustrate that (1) combination of amino acid with aromatic moieties provides a probability for improving antibacterial activity, and (2) these compounds in ammonium form and with prnethyl phenyl group may have the highest activity.…”
mentioning
confidence: 98%
“…Combining the aromatic moiety and a-amino acid, we prepared aromatic amino acids in 1993. 4 The results of the antibacterial tests for Escherichia cola and Staphylococcus uufeus showed that the activity of these compounds in ammonium form was higher than that in carboxylic form and the compounds with prnethylphenyl group were more active than those with o-methylphenyl group. These results illustrate that (1) combination of amino acid with aromatic moieties provides a probability for improving antibacterial activity, and (2) these compounds in ammonium form and with prnethyl phenyl group may have the highest activity.…”
mentioning
confidence: 98%
“…Recently, amino acid esters and amides have been a subject of intensive investigations owing to their excellent emulsifying properties, biocompatibility, and strong antimicrobial activity (6)(7)(8)(9)(10)(11)(12)(13)(14). These features have made them attractive for applications in cosmetics and personal-care products, food, and pharmaceutical formulations.…”
mentioning
confidence: 99%